Resin film and method for producing the same
By applying different resin compositions to the central part and both end parts of the polyimide film and processing, the problem of deterioration of the sliding properties and optical properties of the polyimide film in the prior art is solved, and high sliding properties are achieved Combined with mechanical strength, it is suitable for highly functional electronic/optical equipment.
Patent Information
- Application Number
- CN202180037009.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-03
- Filing Date
- 2021-07-01
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-07-01
AI Technical Summary
The prior art can easily lead to deterioration of optical properties when improving the transparency and sliding properties of the polyimide film, and the increase in the amount of inorganic particles added in the existing method will affect the mechanical strength and optical properties of the film.
The first resin composition solution is coated in the center of the support and the second resin composition solution containing inorganic particles at both ends. The cutting-off film laminate is formed by drying, and then removed by a tenter conveying device. The second resin composition solution is formed to ensure that the content of inorganic particles at both ends is higher than that of the central part, and the sliding properties and mechanical strength are improved while maintaining transparency.
It realizes that the sliding properties of the polyimide film are improved without damaging transparency and mechanical strength, avoids wrinkles and slack problems, and can effectively suppress coiling defects. It is suitable for highly functional electronic/optical equipment. .
Smart Images

Figure CN115697575B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a resin film having good transparency, heat resistance and mechanical strength and a method for producing the same, and in particular, to a polyimide film and a method for producing the same, wherein a substrate for optical components using the film can be used in electronic / optical devices such as liquid crystal displays, organic electroluminescent elements, and electronic paper. Background Art
[0002] In recent years, as highly functional mobile phones, display devices, and various other electronic components have become smaller and lighter, expectations have been growing for transparent resin substrate materials that can replace conventional glass substrates.
[0003] In order to be applicable to these applications, in addition to the transparency, heat resistance, and strength that are the characteristics of conventional glass substrates, a form that can be industrially produced and used is required.
[0004] When the grade of these films is ensured and they are used in industry, one of the important practical properties is the slipperiness of the film. In thin films with smooth surfaces, very high friction occurs when the films come into contact with each other. Therefore, when the film is rolled into a coil, if the slipperiness is poor, wrinkles and other poor appearances are likely to occur. By ensuring the slipperiness of the film support (such as a roller) and the film or the slipperiness between the films, the operability and handling in each process are improved, and the generation of wrinkles and other poor parts on the film can be avoided.
[0005] As a method for imparting slipperiness to a film, there is a method of adding inorganic fine powder to the film to form fine protrusions on the surface, as described in Patent Document 1. Alternatively, as described in Patent Document 2, a film having improved slipperiness is obtained by coating a polyamic acid solution, which is a raw material for a polyimide film, on the surface of a support to form irregularities.
[0006] As a technique for making a polyimide film that is required to be transparent easy to slide, there is a method of adding fine particles such as alumina and silica having a volume average particle diameter in the range of 5 nm to 100 nm (Patent Document 3).
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Publication No. 6-11800
[0010] Patent Document 2: Japanese Patent Application Publication No. 2002-234040
[0011] Patent Document 3: Japanese Patent Application Publication No. 2008-292751 Summary of the invention
[0012] Problem that the invention aims to solve
[0013] However, the protrusions formed on the film surface in the method of Patent Document 1 deteriorate the optical properties. The method of Patent Document 2 is also the same, and the protrusions transferred to the film surface deteriorate the optical properties. In addition, in the method of Patent Document 3, the amount of addition required to obtain the necessary slippage increases when the particle size is small, and the increase in the amount of addition has other problems that the optical properties of the film deteriorate.
[0014] The present invention is produced in view of the above-mentioned problems, and its purpose is to provide a method for manufacturing a polyimide film that can be industrially produced, and a polyimide film with excellent transparency that can be used as a transparent resin substrate used in highly functional mobile phones and display devices and other various electronic components.
[0015] Technical solutions to the problem
[0016] The present inventors have conducted intensive research on a method for producing a resin film and a film before cutting, and have found that by adopting the following composition, when a film having excellent transparency is wound into a roll, appearance defects such as wrinkles can be suppressed, thereby achieving the present invention.
[0017] That is, the method for producing a resin film according to the present invention comprises the following composition.
[0018] [1] A method for producing a resin film, comprising:
[0019] Step A of applying a first resin composition solution to the center of the support,
[0020] Step B of applying a second resin composition solution containing inorganic fine particles to both end portions adjacent to the central portion,
[0021] Step C of drying the first resin composition solution and the second resin composition solution to obtain a pre-cut film laminate,
[0022] A step D of peeling the pre-cutting film laminate from the support to obtain a pre-cutting film,
[0023] After the step D, the two ends of the pre-cut film are held by a tenter conveyor.
[0024] A step F of conveying the pre-cut film while holding both ends of the pre-cut film, and
[0025] After the step F, a step G of removing part or all of the portion formed by the second resin composition solution from the pre-cut film,
[0026] The content of the inorganic fine particles in the two end portions is greater than the content of the inorganic fine particles in the central portion.
[0027] [2] The method for producing a resin film described in [1], wherein the film thickness at the two end portions is greater than the film thickness at the center portion.
[0028] [3] The method for producing a resin film according to [1] or [2], wherein the first resin composition is a polyimide-based resin.
[0029] [4] A pre-cut film, characterized in that it has: a central portion composed of a first resin composition, and two end portions formed continuously from the central portion at both ends of the central portion,
[0030] The two end portions are formed of a second resin composition containing inorganic fine particles, and the content of the inorganic fine particles in the two end portions is greater than the content of the inorganic fine particles in the central portion.
[0031] [5] The pre-cut film described in [4] is characterized in that the film thickness at the two end portions is greater than the film thickness at the center portion.
[0032] [6] The pre-cut film according to [5] or [6], wherein the first resin composition is a polyimide-based resin.
[0033] [7] A partially cut film having a cut portion on the pre-cut film according to [5] or [6].
[0034] According to the composition, the first resin composition solution is applied to the central part of the support (process A), and the second resin composition solution containing inorganic particles is applied to the two ends (process B), and the first resin composition solution and the second resin composition solution are dried to obtain a film laminate before cutting (process C). The two ends of the film laminate before cutting are parts formed only by the second resin composition solution. Here, the amount of inorganic particles contained in the second resin composition solution needs to be more than the amount of inorganic particles contained in the first resin composition solution. Thus, the friction coefficient of the two ends can be smaller than the friction coefficient of the central part. Further, the film thickness of the two ends formed by the second resin composition solution is preferably thicker than the film thickness of the central part formed by the first resin composition. By making the film thickness of the two ends thicker than the film thickness of the central part, when the film is rolled up, stronger contact occurs compared to the two ends of the central part, and it can be rolled up without wrinkles or relaxation in the film.
[0035] The process D of obtaining the pre-cut film by further peeling the pre-cut film laminate from the support body; after the process D, the process E of holding the two ends of the pre-cut film by a tenter conveyor; the process F of conveying the pre-cut film while the two ends of the pre-cut film are held; and after the process F, the process G of removing part or all of the part formed by the second resin composition solution from the pre-cut film to obtain the resin film. Here, the resin film from which part of the part formed by the second resin composition solution is removed is called "partially cut film", and the resin film from which all is removed is called "fully cut film". That is, the resin film has a cut portion (cut surface). According to such a method, the pre-cut film and the partially cut film, even if the film has low slippage in the central portion, can be wound up without defects such as wrinkles even if an existing well-known winding device is used due to the excellent slippage of the two ends.
[0036] In the above configuration, the step E is preferably a step of gripping both end portions of the pre-cut film by pins of a pin tenter feed device.
[0037] The film before cutting and the partially cut film preferably have a film thickness of the portion (the two ends) formed by the second resin composition solution greater than the film thickness of the portion (the central portion) formed by the first resin composition solution. This improves the mechanical strength of the two ends, and, for example, can better suppress cracking caused by the needles of a pin tenter conveyor.
[0038] In the above composition, the resin film is preferably a polyimide-based resin film.
[0039] In recent years, there is a high need for the high transparency polyimide resin film, and such polyimide resin film has a reduced transparency due to the addition of inorganic particles. Therefore, according to the composition, the first resin composition solution (central portion) also contains inorganic particles, and particularly, a polyimide resin film with excellent transparency can be suitably obtained.
[0040] In addition, the pre-cut film and the partially cut film according to the present invention are characterized by having:
[0041] a central portion composed of a first resin composition, and
[0042] At both ends of the central portion, two end portions are formed continuously from the central portion,
[0043] The two end portions are formed of the second resin composition having a larger content of inorganic fine particles than the first resin composition. In a more preferred configuration, the film thickness of the two end portions is thicker than the film thickness of the central portion.
[0044] According to the above composition, since the content of the inorganic fine particles in the both end portions is larger than that in the central portion, even if the film has low slip properties in the central portion, the slip properties in the both end portions are excellent.
[0045] In addition, according to a more preferred composition, since the film thickness at both ends of the film before cutting is thicker than that in the central portion, when a portion of the two ends is removed to obtain a partially cut film, the two ends remaining in the film will have stronger contact than the two ends of the central portion when winding up, and even if an existing publicly known winding device is used, it can be wound up without defects such as wrinkles.
[0046] In the above composition, the first resin composition is preferably a polyimide-based resin.
[0047] When the first resin composition is a polyimide resin, a polyimide resin film having a central portion with excellent transparency can be preferably obtained by removing a portion of both end portions after conveying the composition through a tenter conveyor.
[0048] Effects of the Invention
[0049] According to the present invention, a method for producing a resin film, a film before cutting, and a resin film can be provided that can effectively suppress winding defects such as wrinkles in the film even when a film having excellent transparency is wound using a conventionally known winding device. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] [ Figure 1 ] is a side cross-sectional view used to illustrate the coating method of the resin composition solution involved in the first embodiment.
[0051] [ Figure 2 ] Figure 1 Floor plan.
[0052] [ Figure 3 ] Figure 2 A partial enlarged plan view of the vicinity of the side plate 18b is shown in FIG.
[0053] [ Figure 4 ] shows a cross-sectional view when only the side surfaces of each coating film are connected.
[0054] [ Figure 5 ] shows a cross-sectional view when the coating film 64a and the coating film 64c slightly overlap on the coating film 64b.
[0055] [ Figure 6 ] shows a cross-sectional view when the coating film 64b slightly overlaps the coating film 64a and the coating film 64c.
[0056] [ Figure 7 ] is a side cross-sectional view used to illustrate the coating method of the resin composition solution involved in the second embodiment.
[0057] [ Figure 8 ] Figure 7 Floor plan.
[0058] [ Fig. 9 ] is a side cross-sectional view used to illustrate the coating method of the resin composition solution involved in the third embodiment.
[0059] [ Fig.10 ] Fig. 9 Floor plan.
[0060] [ Fig.11 ] shows a cross-sectional view in which an end portion of the coating film 64a slightly overlaps the coating film 64b, and an end portion of the coating film 64b slightly overlaps the coating film 64c.
[0061] [ Fig.12 ] is a side cross-sectional view used to illustrate the coating method of the resin composition solution involved in the fourth embodiment.
[0062] [ Fig.13 ] Fig.12 Floor plan. DETAILED DESCRIPTION
[0063] Hereinafter, embodiments of the present invention will be described.
[0064] [Method for producing resin film]
[0065] The method for producing a resin film according to the present embodiment includes:
[0066] Step A of applying a first resin composition solution to the central portion of the support,
[0067] Step B of applying a second resin composition solution containing inorganic fine particles to both end portions adjacent to the central portion,
[0068] Step C of drying the first resin composition solution and the second resin composition solution to obtain a pre-cut film laminate,
[0069] A step D of peeling the pre-cutting film laminate from the support to obtain a pre-cutting film,
[0070] After the step D, a step E is performed in which both ends of the film before cutting are held by a tenter conveyor.
[0071] A step F of conveying the pre-cut film while holding both ends of the pre-cut film, and
[0072] After the step F, a step G of removing part or all of the portion formed by the second resin composition solution from the pre-cut film,
[0073] The content of the inorganic fine particles in the two end portions is greater than the content of the inorganic fine particles in the central portion.
[0074] <Process A, Process B>
[0075] In the manufacturing method of the resin film involved in the present embodiment, first, the first resin composition solution is applied to the central portion of the support (process A). In addition, the second resin composition solution containing inorganic particles is applied to the two ends adjacent to the central portion (process B). The process A and the process B can be performed simultaneously, or the process A can be performed after the process B, or the process A can be performed after the process B. The second resin composition solution needs to contact the two ends of the first resin composition solution.
[0076] The support is not particularly limited, but is preferably a product resistant to the solvent of the first resin composition solution and the second resin composition solution, and examples thereof include PET (polyethylene terephthalate) resin films, metal drums, and endless steel belts.
[0077] The coating method of the step A and the step B is not particularly limited, and for example, comma coating, T-die coating, spin coating, spray coating, rod coating, blade coating, dip coating, etc. can be cited. Two methods can also be combined from these. Comma coating, T-die coating, or a combination of these is preferred from the viewpoint of productivity.
[0078] Hereinafter, specific examples of the step A and the step B will be described.
[0079] [First embodiment]
[0080] Figure 1 is a side cross-sectional view for explaining the coating method of the resin composition solution involved in the first embodiment, Figure 2 For its floor plan.
[0081] like Figure 1 , Figure 2 As shown, the coating device 10 includes a backup roll 12, a comma roll 14, and three coating liquid storage portions 16 (16a, 16b, 16c).
[0082] The coating liquid storage section 16 (16a, 16b, 16c) has four side plates 18 (18a, 18b, 18c, 18d) and a back plate 20 for dividing the coating liquid storage section 16. The coating liquid storage section 16 (16a, 16b, 16c) can store the coating liquid 62 in the area surrounded by the back plate 20 and the side plates 18.
[0083] Of the three coating liquid storage sections 16 (16a, 16b, 16c), the coating liquid storage sections 16a and 16c located at both ends store the second resin composition solutions 62a and 62c, and the coating liquid storage section 16b located in the center stores the first resin composition solution 62b.
[0084] The support roller 12 continuously conveys the support body 60 by rotating. The support body 60 conveyed by the support roller 12 passes through the gap 22 formed between the support roller 12 and the comma roller 14. When the support body 60 passes through the gap 22, the coating liquid 62 (the second resin composition solution 62a, 62c, the first resin composition solution 62b) is supplied from the coating liquid storage part 16 to the support body 60 to form a coating film 64 (64a, 64b, 64c). Specifically, the coating film 64 having a thickness equivalent to the thickness of the support body 60 minus the thickness of the gap 22 is formed.
[0085] The thickness of the coating film 64 can be controlled by the gap 22 between the backup roll 12 and the comma roll 14 and the like.
[0086] Figure 3 for Figure 2 A partial enlarged plan view of the vicinity of the side plate 18b is shown in FIG.
[0087] After each coating liquid 62 (second resin composition solution 62a, 62c, first resin composition solution 62b) is coated on the support 60, it is extended in the width direction. Specifically, Figure 3 As shown, the second resin composition solution 62a applied near the side plate 18b is spread inward in the width direction ( Figure 2 , Figure 3 On the other hand, the first resin composition solution 62b applied near the side plate 18b extends outward in the width direction ( Figure 2 , Figure 3 Then, the mechanical direction ( Figure 2 , Figure 3 In the portion without the side plate 18b (the upper side in the middle), the second resin composition solution 62a (coating film 64a) is connected to the first resin composition solution 62b (coating film 64b).
[0088] Similarly, the first resin composition solution 62b applied near the side plate 18c is spread outward in the width direction ( Figure 2 On the other hand, the second resin composition solution 62c applied near the side plate 18c extends inward in the width direction ( Figure 2 Then, in the portion without the side plate 18c in the machine direction, the first resin composition solution 62b (coating film 64b) and the second resin composition solution 62c (coating film 64c) are connected.
[0089] As described above, coating film 64a is connected to coating film 64b, and coating film 64b is also connected to coating film 64c. The connection can be exemplified by the case where the resin composition solutions forming each coating film 64 are connected by mutual dissolution, and the case where the interfaces of each coating film 64 are connected by adhesive force.
[0090] The connection method of each coating film 64 is not particularly limited, and an example thereof is a case where each coating film is connected only at the side ( Figure 4 Reference), when any coating film slightly overlaps the other coating film ( Figure 5 , Figure 6 As a more preferred connection method, Figure 4 or Figure 5 , as a particularly preferred connection method is Figure 5 .
[0091] Figure 4 This is a cross-sectional view showing that the film thickness at both ends is almost the same as that at the center, and that the respective coating films are connected only at the side surfaces.
[0092] Figure 4 In the example shown, the coating film 64a and the coating film 64b are connected only on the side. In addition, the coating film 64b and the coating film 64c are connected only on the side. Just after coating, only the side is connected, but until just before the subsequent process C, the second resin composition solution 62a (coating film 64a) and the first resin composition solution 62b (coating film 64b), or the first resin composition solution 62b (coating film 64b) and the second resin composition solution 62c (coating film 64c) are mixed to form a component gradient region. The width of the component gradient region is preferably in the range of 10 to 2500 times the thickness of the coating film 64b in the non-component gradient region. More preferably, it is 100 to 1000 times, and more preferably 250 to 500 times. For example, when the coating film 64b is 20 μm thick, the width of the composition gradient region is preferably 0.2 mm (10 times the thickness of the coating film 64b) to 5 cm (2500 times the thickness of the coating film 64b). Within this range, cracks are less likely to occur in the composition gradient region during manufacturing.
[0093] Figure 5 This is a cross-sectional view showing that the film thickness at both ends is larger than the film thickness at the center, and the coating film 64a and the coating film 64c slightly overlap on the coating film 64b.
[0094] Figure 5In the example shown, the end of the coating film 64a overlaps slightly on the coating film 64b. In addition, the end of the coating film 64c overlaps slightly on the coating film 64b. The overlapping portion is a component gradient region formed by the mixing of the second resin composition solution 62a (coating film 64a) and the first resin composition solution 62b (coating film 64b), or the first resin composition solution 62b (coating film 64b) and the second resin composition solution 62c (coating film 64c). The width of the component gradient region is preferably in the range of 10 to 2500 times the thickness of the coating film 64b in the non-component gradient region. More preferably, it is 100 to 1000 times, and further preferably 250 to 500 times. For example, when the thickness of the coating film 64b is 20 μm, the width of the component gradient region is preferably 0.2 mm (10 times the thickness of the coating film 64b) to 5 cm (2500 times the thickness of the coating film 64b). If the composition gradient region is produced within this range, it is not easy to break. In addition, when the resin film is wound into a coil, the films in the central part do not rub against each other, and wrinkles and looseness are not easy to occur.
[0095] Figure 6 This is a cross-sectional view showing that the film thickness at both ends is smaller than the film thickness at the center, and the coating film 64b slightly overlaps the coating film 64a and the coating film 64c.
[0096] Figure 6 In the example shown, the end portion ( Figure 6 The end portion (the left end portion in the figure) slightly overlaps the coating film 64a. Figure 6 The right end in the middle) slightly overlaps the coating film 64c. As an example of the width of the overlapping portion, Figure 5 As in the case of , it is preferably in the range of 10 to 2500 times that of the coating film 64b in the non-composition gradient region. It is more preferably 100 to 1000 times, and further preferably 250 to 500 times. If it is in this range, it is not easy to generate a break from the composition gradient region during manufacturing.
[0097] The connection method can be determined, for example, by the gap 22. If the gap 22 through which the second resin composition solutions 62a and 62c pass is the same as the gap 22 through which the first resin composition solution 62b passes, it is easy to form Figure 4 By making the gap 22 through which the second resin composition solutions 62a and 62c pass slightly larger than the gap 22 through which the first resin composition solution 62b passes, it is easy to become Figure 5 By making the gap 22 through which the first resin composition solution 62b passes slightly larger than the gap 22 through which the second resin composition solutions 62a and 62c pass, it is easy to form Figure 6It should be noted that the connection method can be controlled not only by the gap 22 but also by the viscosity of the first resin composition solution 62b, the second resin composition solution 62a, 62c and the width of the side plate 18.
[0098] In the first embodiment, according to the coating apparatus 10 described above, step A and step B are performed simultaneously.
[0099] In the above, the step A and the step B according to the first embodiment have been described.
[0100] [Second embodiment]
[0101] Figure 7 is a side cross-sectional view for explaining a method for applying a resin composition solution according to a second embodiment. Figure 8 It is to be noted that, in the coating device 30 of the second embodiment, the same reference numerals are given to the common configurations with the coating device 10 of the first embodiment, and the description thereof is omitted or simplified.
[0102] like Figure 7 , Figure 8 As shown, the coating device 30 includes a support roller 12, a comma roller 14, and two coating liquid storage sections 16 (16a, 16c) on both sides in the width direction. The coating liquid storage sections 16 (16a, 16c) can store the coating liquid 62 in the area surrounded by the back plate 20 and the side plates 18.
[0103] The two coating liquid storage parts 16 (16a, 16c) store the second resin composition solutions 62a, 62c. It should be noted that, unlike the first embodiment, in the coating device 30 according to the second embodiment, the coating liquid storage part 16 does not store the first resin composition solution.
[0104] The support roller 12 continuously conveys the support 60 by rotating. The support 60 conveyed by the support roller 12 passes through the gap 22 formed between the support roller 12 and the comma roller 14. When the support 60 passes through the gap 22, the second resin composition solution 62a, 62c is supplied from the coating liquid storage part 16 to the support 60, and the coating films 64a, 64c are formed.
[0105] The coating device 30 further includes a T-die coater 32. The T-die coater 32 is provided at a stage after the support roll 12 and the comma roll 14. The T-die coater 32 is provided so that the discharge port is located above the center of the support 60.
[0106] When the support 60 on which the coating films 64 a and 64 c are formed is conveyed, the T-die coater 32 applies the first resin composition solution 62 b on the center portion of the support 60 .
[0107] In the second embodiment, the coating device 30 described above is used to first perform step B and then perform step A. In the second embodiment, the connection method of each coating film 64 is easy to be Figure 6 It should be noted that, as a modification of the second embodiment, the first resin composition solution may be firstly applied with a comma coater in the central portion of the support, and then the second resin composition solution may be applied with a T-die coater at both ends.
[0108] In the above, the step A and the step B according to the second embodiment have been described.
[0109] [Third Embodiment]
[0110] Fig. 9 is a side cross-sectional view for explaining a method for applying a resin composition solution according to a third embodiment. Fig.10 It is to be noted that, in the coating device 40 of the third embodiment, the same components as those of the coating device 30 of the second embodiment are denoted by the same reference numerals and their description is omitted or simplified.
[0111] The coating device 40 includes a T-die coater 42a, a T-die coater 42b, and a T-die coater 42c. The T-die coater 42a and the T-die coater 42c are provided at a front stage compared to the T-die coater 42b.
[0112] The T-die coaters 42 a and 42 c are respectively provided so that their discharge ports are located above the end portions of the support body 60 . Fig.10 In the figure, the T-die coater 42 a is arranged so that the discharge port is located above the left end of the support body 60 , and the T-die coater 42 c is arranged so that the discharge port is located above the right end of the support body 60 .
[0113] The T-die coater 42 b is provided so that the discharge port is located above the center of the support 60 .
[0114] When the support 60 on which the coating films 64 a and 64 c are formed is conveyed, the T-die coater 42 b applies the first resin composition solution 62 b to the center portion of the support 60 .
[0115] In the case of the third embodiment, the coating films 64 can be easily joined in the following manner: Figure 5 In addition, as a modification of the third embodiment, the second resin composition may be applied to both ends by a T-die coater, and then the first resin composition may be applied to the center by a T-die coater. In this case, the coating films 64 may be easily joined in the following manner: Figure 6The joining method shown in, but not limited to this.
[0116] Furthermore, as another modification, the second resin composition can be applied to one end portion by a T-die coater, and then the first resin composition can be applied to the center portion by a T-die coater, and then the second resin composition can be applied to one end portion by a T-die coater on the other end portion. In this case, the joining method of each coating film 64 is easy to be Fig.11 The joining method shown in, but not limited to this.
[0117] Fig.11 In the example shown, the end of the coating film 64a slightly overlaps the coating film 64b. Fig.11 The right end in the middle) slightly overlaps the coating film 64c.
[0118] As shown in the third embodiment and its modified example, in step A and step B, a plurality of T-die coaters may be arranged in a row to sequentially coat the first resin composition and the second resin composition.
[0119] [Fourth embodiment]
[0120] Fig.12 : is a side cross-sectional view for explaining the coating method of the resin composition solution involved in the fourth embodiment, Fig.13 It is to be noted that the same reference numerals are given to the common configurations of the coating device 50 of the fourth embodiment and the coating device 40 of the third embodiment, and the description thereof will be omitted or simplified.
[0121] The coating device 50 has a T-die coater 52 having three discharge ports divided in the width direction. The T-die coater 52 coats the first resin composition on the center portion of the support 60 and coats the second resin composition on both end portions.
[0122] like Fig.12 , Fig.13 As shown, the steps A and B in the fourth embodiment are a method of applying the first resin composition and the second resin composition at the same time. In the case of the fourth embodiment, the bonding method of each coating film 64 is easy to be as follows Figure 4 The joining method shown in, but not limited to this.
[0123] <Process C>
[0124] After the steps A and B, the first resin composition solution and the second resin composition solution are dried to obtain a pre-cut film laminate (step C). The drying conditions can be appropriately set within a range that allows the solvent to fully volatilize. For example, the drying temperature can be in the range of 60°C to 140°C and the drying time can be in the range of 1 minute to 60 minutes. The drying conditions are particularly preferred when dimethylacetamide is used as a solvent because it has a boiling point of 165°C.
[0125] Alternatively, after step C and before step D, a step (step C-1) of winding the pre-cut film laminate together with the support body into a coil may be performed. In this case, before step D, the pre-cut film can be unwound again. In addition, in the present invention, the content of inorganic particles at the two end portions is greater than that at the central portion. Therefore, if the Figure 4 or Figure 5 The composition of the rubber sheet can prevent wrinkles and looseness in the central part because the sliding properties (friction coefficient) of the two end parts are greater than that of the central part.
[0126] <Process D>
[0127] After the step C, the pre-cut film laminate is peeled off from the support to obtain the pre-cut film (step D). There is no particular limitation on the method of peeling the pre-cut film laminate from the support, and the method of rolling up from the end using tweezers or the like, the method of cutting the pre-cut film laminate, attaching an adhesive tape to one side of the cut portion, and then rolling up from the tape portion, and the method of vacuum-adsorbing one side of the cut portion of the pre-cut film and then rolling up from the portion, etc. As the method of rolling up, it is preferred to roll up while rolling with a roller.
[0128] As a method of cutting the pre-cut film laminate, there are methods of cutting the pre-cut film laminate with a cutting tool such as a knife, a method of cutting the pre-cut film laminate by relative scanning of a laser and the laminate, a method of cutting the pre-cut film laminate by relative scanning of a water jet and the laminate, etc., and the method is not particularly limited. For example, when adopting the above methods, it is also possible to appropriately use techniques such as adding ultrasonic waves to the cutting tool, applying back and forth motions and up and down motions, etc. to improve cutting performance.
[0129] After step D and before step E, a step of winding the pre-cut film into a coil (step D-1) may also be performed. In this case, before step E, the pre-cut film can be unwound again. When winding the pre-cut film, it is preferred to wind it with a backing paper (anti-adhesion film) sandwiched between them. Figure 4 or Figure 5The composition of the rubber sheet can prevent wrinkles and looseness in the central part because the sliding properties (friction coefficient) of the two end parts are greater than that of the central part.
[0130] If the step C-1 and / or the step D-1 is performed, it can be set within a certain period of time after the drying step (step C) and before the cutting step (step G) is performed.
[0131] After the drying step (step C), the cut film stack is wound up once and kept in this state for a certain period of time, so that the solvent distribution in the thickness direction of the film can be made uniform. This point will be described below.
[0132] like Figure 5 , Figure 6 As shown in the figure, when two coating films are slightly overlapped, the solvent distribution in the film just dried on the support is that the residual amount of solvent in the coating film on the support side is greater than the residual amount of solvent in the coating film on the surface side. If a heating step (such as step F described later) is performed in this state, a difference in the amount of solvent volatilization occurs, and this part (overlapping part) becomes easy to crack.
[0133] Therefore, by carrying out the steps C-1 and / or D-1, the solvent distribution in the thickness direction of the overlapping portion is equalized, and the residual solvent amounts of the two coating films become relatively equal, so that the overlapping portion is less likely to crack.
[0134] After the step C-1 and / or the step D-1, the coil state is preferably maintained for 30 minutes or longer, more preferably 3 hours or longer. If the coil state is maintained for the above period, the solvent can be appropriately diffused in the thickness direction.
[0135] In addition, if the steps C-1 and / or D-1 are implemented, the production device can be miniaturized because the pre-cut film is once wound up during the process. That is, if all steps are connected continuously, it will become a very long production line, which will limit the factory layout. On the other hand, if the winding process is implemented during the manufacturing process, the production line can be divided into two, and the two divided production lines can be arranged in parallel, which can become a relatively small manufacturing device.
[0136] Furthermore, by winding up once during the manufacturing process, quality inspection during the process becomes possible.
[0137] <Process E>
[0138] After the step D, both ends of the film before cutting are held by a tenter conveyor (step E). Specifically, when a pin tenter conveyor is used as the tenter conveyor, both ends of the film before cutting are held by piercing a plurality of needles of the pin tenter conveyor. Also, when a clip tenter conveyor is used as the tenter conveyor, both ends of the film before cutting are held by clamping a plurality of clips of the clip tenter conveyor. As the tenter conveyor, a conventionally known device (for example, a tenter conveyor disclosed in Patent Gazette No. 4843996 and Patent Gazette No. 4821960) can be used.
[0139] <Process F>
[0140] After the step E, the pre-cut film is conveyed while both ends of the pre-cut film are held (step F). The film may be heated during conveyance. The heating temperature is not particularly limited, and when the first resin composition solution and the second resin composition solution are polyimide resin composition solutions, for example, the heating temperature can be within the range of 150° C. to 500° C. and 1 minute to 60 minutes.
[0141] In addition, in step E and step F, the film before cutting may be stretched in the width direction or may not be stretched.
[0142] In the process F, the film before cutting usually shrinks in the width direction during transportation. Therefore, tensile tension is applied to the holding part in the tenter conveyor. Since the film thickness at the two ends of the film before cutting is preferably thicker than the film thickness at the central part, the cracking of the film before cutting on the holding part (two ends) can be suppressed. In addition, in the film before cutting, by making the tear strength of the two ends (the parts formed by the second resin composition solution) greater than the tear strength of the central part (the part formed by the second resin composition solution), the cracking of the film before cutting in the holding part (two ends) can be further suppressed. In particular, when a pin tenter conveyor is used as a tenter conveyor, the cracking caused by the needles of the pin tenter conveyor is better suppressed.
[0143] <Process G>
[0144] After the step F, a part or all of the portion formed by the second resin composition solution is removed from the film before cutting to obtain a resin film (step G). In step G, at least a part or all of the portion formed by the second resin composition solution may be removed, and a part of the portion formed by the first resin composition solution may be removed together with the portion formed by the second resin composition solution. That is, the resin film may remove a part or all of both ends from the composition of "end / central part / end", for example, it may be any one of "end / central part / end with a portion cut off", "end / central part with a portion cut off / central part / end with a portion removed", "end / central part", "end / central part with a portion cut off", "central part" or "central part with a portion cut off".
[0145] The film thickness (thickness) of the central part of the film before cutting is not particularly limited, but is preferably 5μm to 125μm, more preferably 7.5μm to 75μm, and further preferably 12.5μm to 50μm. In addition, the film thickness (thickness) of the two end portions is not particularly limited, but is preferably 10μm to 200μm, more preferably 15μm to 180μm, and further preferably 20μm to 150μm. The film thickness of each end portion may be the same or different, and is preferably the same. The film thickness of each end portion is preferably greater than the film thickness of the central portion. The ratio of the film thickness of each end portion to the film thickness of the central portion (two end portions / central portion) is preferably greater than 1. In order to easily prevent wrinkles and sags in the central portion, it is more preferably 1.25 or more, and further preferably 1.5 or more. In addition, in order to make the dry state of the two end portions and the central portion have no difference, it is preferably 20 or less, more preferably 10 or less, and further preferably 5 or less. The film thickness in the film before cutting is the film thickness of the resin film.
[0146] There is no particular limitation on the method for removing the portion formed from the second resin composition solution from the pre-cut film, and a conventionally known cutter or the like can be used. At this time, a cut portion (cut surface) is generated.
[0147] As described above, according to the method for producing a resin film according to the present embodiment, even when a film having excellent transparency is wound up using a conventionally known winding device, winding defects such as wrinkles generated in the film can be effectively suppressed.
[0148] Hereinafter, the first resin composition solution and the second resin composition solution (hereinafter also referred to as “resin composition solution”) will be described.
[0149] The first resin composition solution and the second resin composition solution are not particularly limited as long as the content of inorganic particles in the pre-cut film and the resin film formed by the second resin composition solution is greater than the content of inorganic particles in the part formed by the first resin composition solution.
[0150] Examples of the resin composition solution include polyimide resin composition solutions, polyamide resin composition solutions, polyamideimide resin composition solutions, polyester resin composition solutions, polyolefin resin composition solutions, polystyrene resin composition solutions, etc. Among them, polyimide resin composition solutions are preferred due to their good transparency, heat resistance, and mechanical strength.
[0151] The polyimide resin composition solution may be a polyamic acid (polyimide precursor) solution or a polyimide solution. When a polyamic acid solution is used, a dehydration ring-closure reaction is performed by heat treatment in step F to form a polyimide film. When a polyimide solution is used, a polyimide film is formed by volatilizing the solvent in step C.
[0152] The polyimide film in the present invention is a polymer film having an imide bond in the main chain, preferably a polyimide film, a polyamideimide film, or a polyamide film, more preferably a polyimide film or a polyamideimide film, and even more preferably a polyimide film.
[0153] Usually, the polyimide film is obtained by coating a polyamic acid (polyimide precursor) solution obtained by reacting diamines and tetracarboxylic acids in a solvent on a support for the production of the polyimide film, drying to form a green film (also referred to as a "precursor film" or "polyamic acid film"), and further heat-treating the green film at high temperature on the support for the production of the polyimide film or in a state in which the green film is peeled off from the support for dehydration and ring-closure reaction. In addition, as another method, a polyimide solution obtained by the dehydration and ring-closure reaction of diamines and tetracarboxylic acids in a solvent can be coated on a support for the production of the polyimide film, drying to form a polyimide film containing, for example, 1 to 50% by mass of a solvent, and further treating the polyimide film containing 1 to 50% by mass of a solvent at high temperature on the support for the production of the polyimide film or in a state in which the polyimide film is peeled off from the support to dry it.
[0154] In addition, usually, the polyamide-imide film is obtained by coating a polyamide-imide solution obtained by reacting a diisocyanate and a tricarboxylic acid in a solvent on a support for polyamide-imide film production, drying to form a polyamide-imide film containing, for example, 1 to 50% by weight of the solvent, and further drying the polyamide-imide film containing 1 to 50% by weight of the solvent by high-temperature treatment on the support for polyamide-imide production or in a state peeled off from the support.
[0155] In addition, usually, the polyamide film is obtained by coating a polyamide solution obtained by reacting diamines and dicarboxylic acids in a solvent on a support for polyamide film production, drying to form a polyamide film containing, for example, 1 to 50% by weight of the solvent, and further drying the polyamide film containing 1 to 50% by weight of the solvent by high temperature treatment on the support for polyamide production or in a state of being peeled off from the support.
[0156] As the tetracarboxylic acid, tricarboxylic acid, dicarboxylic acid, aromatic tetracarboxylic acid (including its anhydride), aliphatic tetracarboxylic acid (including its anhydride), alicyclic tetracarboxylic acid (including its anhydride), aromatic tricarboxylic acid (including its anhydride), aliphatic tricarboxylic acid (including its anhydride), aliphatic dicarboxylic acid, aliphatic dicarboxylic acid, alicyclic dicarboxylic acid, etc., which are commonly used in polyimide synthesis, polyimide amide synthesis, and polyamide synthesis, can be used. Among them, aromatic tetracarboxylic anhydride and aliphatic tetracarboxylic anhydride are preferred, and aromatic tetracarboxylic anhydride is more preferred from the viewpoint of heat resistance, and alicyclic tetracarboxylic acid is more preferred from the viewpoint of light transmittance. When tetracarboxylic acid is anhydride, the anhydride structure in the molecule can be 1 or 2, and is preferably anhydride (dianhydride) with 2 anhydride structures. Tetracarboxylic acid, tricarboxylic acid, and dicarboxylic acid can be used alone, or two or more can be used in combination.
[0157] In order to obtain a colorless and highly transparent polyimide in the present invention, examples of the aromatic tetracarboxylic acid include pyromellitic acid, 4,4'-(2,2-hexafluoroisopropylidene)diphthalic acid, 4,4'-oxydiphthalic acid, 3,4'-oxydiphthalic acid, bis(1,3-dioxyylidene-1,3-dihydro-2-benzofuran-5-carboxylic acid)1,4-phenylene, bis(1,3-dioxyylidene-1,3-dihydro-2-benzofuran-5-yl)benzene-1,4-dicarboxylate, 4,4'-[4,4'-(3-oxyylidene-1,3-dihydro-2-benzofuran-1,1-diyl)bis(benzene-1,4-diyloxy)]diphenyl-1,2-dicarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 4 ,4'-[(3-oxyylidene-1,3-dihydro-2-benzofuran-1,1-diyl)bis(toluene-2,5-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-[(3-oxyylidene-1,3-dihydro-2-benzofuran-1,1-diyl)bis(1,4-dimethylbenzene-2,5-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-[4,4'-(3-oxyylidene-1,3-dihydro-2-benzofuran-1,1-diyl)bis(4-isopropyl-toluene-2,5-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-[4,4'-(3-oxyylidene-1,3-dihydro-2-benzofuran-1,1-diyl)bis(naphthalene-1,4-diyloxy)]dibenzene -1,2-dicarboxylic acid, 4,4'-[4,4'-(3H-2,1-benzoxathiol-1,1-dioxide-3,3-diyl)bis(benzene-1,4-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-benzophenonetetracarboxylic acid, 4,4'-[(3H-2,1-benzoxathiol-1,1-dioxide-3,3-diyl)bis(toluene-2,5-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-[(3H-2,1-benzoxathiol-1,1-dioxide-3,3-diyl)bis(1,4-xylene-2,5-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-[4,4'-(3 H-2,1-benzothiolane-1,1-dioxide-3,3-diyl)bis(4-isopropyl-toluene-2,5-diyloxy)]diphenyl-1,2-dicarboxylic acid, 4,4'-[4,4'-(3H-2,1-benzothiolane-1,1-dioxide-3,3-diyl)bis(naphthalene-1,4-diyloxy)]diphenyl-1,2-dicarboxylic acid, 3,3',4,4'-diphenylsulfonetetracarboxylic acid, 3,3',4,4'-biphenyltetracarboxylic acid, 2,3,3',4'-biphenyltetracarboxylic acid, 2,2',3,3'-biphenyltetracarboxylic acid, 2,2'-diphenoxy-4,4',5,5'-biphenyltetracarboxylic acid, pyromellitic acid, 4,4'-[spiro(xanthene-9,9'-fluorene)-2,Tetracarboxylic acids such as 4,4'-[spiro(xanthine-9,9'-fluorene)-3,6-diylbis(oxycarbonyl)]diphthalic acid and their anhydrides. Among these, dianhydrides having two anhydride structures are suitable, and in particular, 4,4'-(2,2-hexafluoroisopropylidene)diphthalic acid dianhydride and 4,4'-oxydiphthalic acid dianhydride are preferred. In addition, aromatic tetracarboxylic acids can be used alone or in combination of two or more. In the case of attaching importance to heat resistance, aromatic tetracarboxylic acids are, for example, preferably 50% by mass or more of the total tetracarboxylic acids, more preferably 60% by mass or more, further preferably 70% by mass or more, and further preferably 80% by mass or more. ,
[0158] Examples of the alicyclic tetracarboxylic acids include 1,2,3,4-cyclobutanetetracarboxylic acid, 1,2,3,4-cyclopentanetetracarboxylic acid, 1,2,3,4-cyclohexanetetracarboxylic acid, 1,2,4,5-cyclohexanetetracarboxylic acid, 3,3',4,4'-bicyclohexyltetracarboxylic acid, bicyclo[2,2,1]heptane-2,3,5,6-tetracarboxylic acid, bicyclo[2,2,2]octane-2,3,5,6-tetracarboxylic acid, bicyclo[2,2,2]oct-7-enyl-2,3,5,6-tetracarboxylic acid, tetrahydroanthracene-2,3,6,7-tetracarboxylic acid, tetradecahydro-1,4:5,8:9,10-trimethanoanthracene-2,3,6,7-tetracarboxylic acid, and decahydronaphthalene-2,3,6,7 -tetracarboxylic acid, decahydro-1,4:5,8-dimethanonaphthalene-2,3,6,7-tetracarboxylic acid, decahydro-1,4-ethyl-5,8-methanonaphthalene-2,3,6,7-tetracarboxylic acid, norbornane-2-spiro-α-cyclopentanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid (also known as "norbornane-2-spiro-2'-cyclopentanone-5'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid"), methylnorbornane-2-spiro-α-cyclopentanone-α'-spiro-2"-(methylnorbornane)-5,5",6,6"-tetracarboxylic acid, norbornane-2- Spiro-α-cyclohexanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid (also known as "norbornane-2-spiro-2'-cyclohexanone-6'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid"), methylnorbornane-2-spiro-α-cyclohexanone-α'-spiro-2"-(methylnorbornane)-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-cyclopropanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-cyclobutanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-cycloheptanone-α'-spiro-2"-norbornane-5,5",6,6, 6"-tetracarboxylic acid, norbornane-2-spiro-α-cyclooctanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-cyclononanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-cyclodecanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-cycloundecanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-cyclododecanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-cyclotridecanone-α'-spiro-2"-norbornane-5,Tetracarboxylic acids such as norbornane-2-spiro-α-cyclotetradeconone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-cyclopentadeconone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-(methylcyclopentanone)-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, and tetracarboxylic acids such as norbornane-2-spiro-α-(methylcyclohexanone)-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, and these anhydrides. In addition, bi-tower type silsesquioxane derivatives containing anhydride groups represented by the structure of formula (1) can also be mentioned. Among these, dianhydrides having two acid anhydride structures are preferred, and in particular, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclohexanetetracarboxylic dianhydride, and 1,2,4,5-cyclohexanetetracarboxylic dianhydride are preferred, 1,2,3,4-cyclobutanetetracarboxylic dianhydride and 1,2,4,5-cyclohexanetetracarboxylic dianhydride are more preferred, and 1,2,3,4-cyclobutanetetracarboxylic dianhydride is further preferred. It should be noted that these can be used alone or in combination of two or more. When transparency is important, alicyclic tetracarboxylic acids are, for example, preferably 50% by mass or more of the total tetracarboxylic acids, more preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more. . ,
[0159] [Chemistry 1]
[0160]
[0161] As tricarboxylic acids, aromatic tricarboxylic acids such as trimellitic acid, 1,2,5-naphthalenetricarboxylic acid, diphenyl ether-3,3',4'-tricarboxylic acid, and diphenyl sulfone-3,3',4'-tricarboxylic acid, or hydrogenated products of the above aromatic tricarboxylic acids such as hexahydrotrimellitic acid, alkylene glycol trimellitates such as ethylene glycol ditrimellitate, propylene glycol ditrimellitate, 1,4-butanediol ditrimellitate, and polyethylene glycol ditrimellitate, and monoanhydrides and esters thereof can be cited. Among these, monoanhydrides having one acid anhydride structure are preferred, and trimellitic acid anhydride and hexahydrotrimellitic acid anhydride are particularly preferred. In addition, these can be used alone or in combination.
[0162] As dicarboxylic acids, aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, 4,4'-oxy dibenzoic acid, or hydrides of the above aromatic dicarboxylic acids such as 1,6-cyclohexanedicarboxylic acid, oxalic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, 2-methylsuccinic acid, and acid chlorides or esters thereof can be cited. Among these, aromatic dicarboxylic acids and hydrides thereof are preferred, and terephthalic acid, 1,6-cyclohexanedicarboxylic acid, and 4,4'-oxy dibenzoic acid are particularly preferred. In addition, dicarboxylic acids can be used alone or in combination.
[0163] In the present invention, there are no particular restrictions on the diamines or isocyanates used to obtain a polyimide with high colorless transparency, and aromatic diamines, aliphatic diamines, alicyclic diamines, aromatic diisocyanates, aliphatic diisocyanates, alicyclic diisocyanates, etc. commonly used in polyimide synthesis and polyamide-imide synthesis can be used. From the viewpoint of heat resistance, aromatic diamines are preferred, and from the viewpoint of transparency, alicyclic diamines are preferred. In addition, if aromatic diamines with a benzoxazole structure are used, while having high heat resistance, high elastic modulus, low thermal shrinkage, and low linear expansion coefficient can also be exhibited. Diamines and isocyanates can be used alone or in combination of two or more.
[0164] Examples of the aromatic diamines include 2,2'-dimethyl-4,4'-diaminobiphenyl, 1,4-bis[2-(4-aminophenyl)-2-propyl]benzene, 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]sulfide, bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1, 1,3,3,3-hexafluoropropane, m-phenylenediamine, o-phenylenediamine, p-phenylenediamine, m-aminobenzylamine, p-aminobenzylamine, 4-amino-N-(4-aminophenyl)benzamide, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 2,2'-trifluoromethyl-4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone Benzophenone, 3,4'-diaminobenzophenone, 4,4'-diaminobenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, bis[4-(4-aminophenoxy)phenyl]methane, 1,1-bis[4-(4-aminophenoxy)phenyl]ethane, 1,2-bis[4-(4-aminophenoxy)phenyl]ethane, 1,1-bis[4-(4-aminophenoxy)phenyl]propane, 1,2-bis[4-(4-aminophenoxy)phenyl]propane, 1,3-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 1,1-bis[4-(4-aminophenoxy)phenyl] 1,3-bis[4-(4-aminophenoxy)phenyl]butane, 1,4-bis[4-(4-aminophenoxy)phenyl]butane, 2,2-bis[4-(4-aminophenoxy)phenyl]butane, 2,3-bis[4-(4-aminophenoxy)phenyl]butane, 2-[4-(4-aminophenoxy)phenyl]-2-[4-(4-aminophenoxy)-3-methylphenyl]propane, 2,2-bis[4-(4-aminophenoxy)-3-methylphenyl]propane, 2-[4-(4-aminophenoxy)phenyl]-2-[4-(4-aminophenoxy)-3,5-dimethylphenyl]propane, 2,2-bis[4-(4-aminophenoxy)-3,5-dimethylphenyl]propane, 2,2-Bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 1,4-bis(3-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis[4-(4-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfoxide, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether, 1,3-bis[4-(4-aminophenoxy)benzoyl]benzene, 1,3-bis[4-(3-aminophenoxy)phenyl] phenoxy)benzoyl]benzene, 1,4-bis[4-(3-aminophenoxy)benzoyl]benzene, 4,4'-bis[(3-aminophenoxy)benzoyl]benzene, 1,1-bis[4-(3-aminophenoxy)phenyl]propane, 1,3-bis[4-(3-aminophenoxy)phenyl]propane, 3,4'-diaminodiphenyl sulfide, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, bis[4-(3-aminophenoxy)phenyl]methane, 1,1-bis[4-(3-aminophenoxy)phenyl]ethane, 1,2-bis[4-(3-aminophenoxy)phenyl]ethane, bis[4-(3-aminophenoxy)phenyl]sulfoxide, 4,4'-bis[3-(4- 4,4'-bis[3-(3-aminophenoxy)benzoyl]diphenyl ether, 4,4'-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]benzophenone, 4,4'-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]diphenyl sulfone, bis[4-{4-(4-aminophenoxy)phenoxy}phenyl]sulfone, 1,4-bis[4-(4-aminophenoxy)phenoxy-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-aminophenoxy)phenoxy-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-trifluoromethylphenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-trifluoromethylphenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-methylphenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-cyanophenoxy)-α,α-dimethylbenzyl]benzene, 3,3'-diamino-4,4'-diphenoxybenzophenone, 4,4'-diamino-5,5'-diphenoxybenzophenone, 3,4'-diamino-4,5'-diphenoxybenzophenone, 3,3'-diamino-4-phenoxybenzophenone, 4,4'-diamino-5-phenoxybenzophenone, 3,4'-diamino-4-phenoxybenzophenone, 3,4'-diamino-5'-phenoxybenzophenone, 3,3'-diamino-4,4'-Bis(diphenyloxy)benzophenone, 4,4'-diamino-5,5'-diphenyloxybenzophenone, 3,4'-diamino-4,5'-diphenyloxybenzophenone, 3,3'-diamino-4-biphenyloxybenzophenone, 4,4'-diamino-5-biphenyloxybenzophenone, 3,4'-diamino-4-biphenyloxybenzophenone, 3,4'-diamino-5'-biphenyloxybenzophenone, 1,3-bis(3-amino-4-phenoxybenzoyl)benzene, 1,4-bis( 3-amino-4-phenoxybenzoyl)benzene, 1,3-bis(4-amino-5-phenoxybenzoyl)benzene, 1,4-bis(4-amino-5-phenoxybenzoyl)benzene, 1,3-bis(3-amino-4-biphenyloxybenzoyl)benzene, 1,4-bis(3-amino-4-biphenyloxybenzoyl)benzene, 1,3-bis(4-amino-5-biphenyloxybenzoyl)benzene, 1,4-bis(4-amino-5-biphenyloxybenzoyl)benzene, 2,6-bis[4-(4-amino-α,α-diphenyl)benzene 4,4'-[9H-fluorene-9,9-diyl]dianiline (also known as 9,9-bis(4-aminophenyl)fluorene), spiro(xanthene-9,9'-fluorene)-2,6-diylbis(oxycarbonyl)]dianiline, 4,4'-[spiro(xanthene-9,9'-fluorene)-2,6-diylbis(oxycarbonyl)]dianiline, 4,4'-[spiro(xanthene-9,9'-fluorene)-3,6-diylbis(oxycarbonyl)]dianiline, 9,10-bis(4-aminophenyl)fluorene ) adenine, 2,4-bis(4-aminophenyl)cyclobutane-1,3-dicarboxylic acid dimethyl ester, a bi-tower type silsesquioxane derivative containing an amino group represented by the structure of formula (2), and an aromatic diamine in which a part or all of the hydrogen atoms on the aromatic ring of the above aromatic diamine are substituted (the substituent is a halogen atom, an alkyl or alkoxy group having 1 to 3 carbon atoms, a cyano group, a halogenated alkyl or alkoxy group having 1 to 3 carbon atoms in which a part or all of the hydrogen atoms of the alkyl or alkoxy group are substituted with halogen atoms), etc., or. In addition, the aromatic diamines having the benzoxazole structure are not particularly limited, and examples thereof include 5-amino-2-(p-aminophenyl)benzoxazole, 6-amino-2-(p-aminophenyl)benzoxazole, 5-amino-2-(m-aminophenyl)benzoxazole, 6-amino-2-(m-aminophenyl)benzoxazole, 2,2'-p-phenylenebis(5-aminobenzoxazole), 2,2'-p-phenylenebis(6-aminobenzoxazole), 1-(5-aminophenyl)benzoxazole, benzoxazole)-4-(6-aminobenzoxazole)benzene, 2,6-(4,4'-diaminodiphenyl)benzo[1,2-d:5,4-d']bisoxazole, 2,6-(4,4'-diaminodiphenyl)benzo[1,2-d:4,5-d']bisoxazole, 2,6-(3,4'-diaminodiphenyl)benzo[1,2-d:5,4-d']bisoxazole, 2,6-(3,4'-diaminodiphenyl)benzo[1,2-d:4,5-d'] bisoxazole, 2,6-(3,3'-diaminodiphenyl)benzo[1,2-d:5,4-d'] bisoxazole, 2,6-(3,3'-diaminodiphenyl)benzo[1,2-d:4,5-d'] bisoxazole, etc. Among these, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 4-amino-N-(4-aminophenyl)benzamide, 4,4'-diaminodiphenyl sulfone, and 3,3'-diaminobenzophenone are particularly preferred. In addition, the aromatic diamines may be used alone or in combination.
[0165] [Chemistry 2]
[0166]
[0167] As alicyclic diamines, for example, 1,4-cyclohexanediamine, 1,4-diamino-2-methylcyclohexane, 1,4-diamino-2-ethylcyclohexane, 1,4-diamino-2-n-propylcyclohexane, 1,4-diamino-2-isopropylcyclohexane, 1,4-diamino-2-n-butylcyclohexane, 1,4-diamino-2-isobutylcyclohexane, 1,4-diamino-2-sec-butylcyclohexane, 1,4-diamino-2-tert-butylcyclohexane, 4,4'-methylenebis(2,6-dimethylcyclohexylamine) and the like can be mentioned. Among these, 1,4-cyclohexanediamine and 1,4-diamino-2-methylcyclohexane are particularly preferred, and 1,4-cyclohexanediamine is more preferred. In addition, alicyclic diamines can be used alone or in combination.
[0168] Examples of the diisocyanates include diphenylmethane-2,4'-diisocyanate, 3,2'- or 3,3'- or 4,2'- or 4,3'- or 5,2'- or 5,3'- or 6,2'- or 6,3'-dimethyldiphenylmethane-2,4'-diisocyanate, 3,2'- or 3,3'- or 4,2'- or 4,3'- or 5,2'- or 5,3'- or 6,2'- or 6,3'-diethyldiphenylmethane-2,4'-diisocyanate, -2,4'-diisocyanate, 3,2'- or 3,3'- or 4,2'- or 4,3'- or 5,2'- or 5,3'- or 6,2'- or 6,3'-dimethoxydiphenylmethane-2,4'-diisocyanate, diphenylmethane-4,4'-diisocyanate, diphenylmethane-3,3'-diisocyanate, diphenylmethane-3,4'-diisocyanate, diphenyl ether-4,4'-diisocyanate, benzophenone-4,4'- diisocyanate, diphenyl sulfone-4,4'-diisocyanate, toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, m-xylene diisocyanate, p-xylene diisocyanate, naphthalene-2,6-diisocyanate, 4,4'-(2,2-bis(4-phenoxyphenyl)propane) diisocyanate, 3,3'- or 2,2'-dimethylbiphenyl-4,4'-diisocyanate, 3,3'- or 2,2'-diethylbiphenyl- Aromatic diisocyanates such as 4,4'-diisocyanate, 3,3'-dimethoxybiphenyl-4,4'-diisocyanate, and 3,3'-diethoxybiphenyl-4,4'-diisocyanate, and hydrogenated diisocyanates selected from these (for example, isophorone diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and hexamethylene diisocyanate). Among these, diphenylmethane-4,4'-diisocyanate, toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, 3,3'-dimethylbiphenyl-4,4'-diisocyanate, naphthalene-2,6-diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and 1,4-cyclohexane diisocyanate are preferred from the viewpoints of low hygroscopicity, dimensional stability, price, and polymerizability. In addition, the diisocyanates may be used alone or in combination of a plurality thereof.
[0169] The first resin composition solution and the second resin composition solution may be the same or different from each other. Wherein, when a polyimide resin composition solution is used as the first resin composition solution, from the viewpoint of similar heat resistance, a polyimide resin composition solution is preferably used as the second resin composition solution. More preferably, the second resin composition solution has a heat resistance equal to or higher than that of the first resin composition solution. In addition, the second resin composition solutions used in the two ends may be the same or different from each other, preferably polyimide resin composition solutions of the same composition.
[0170] The first resin composition solution may contain inorganic particles. In order to easily obtain a polyimide resin film with high transparency, the content is preferably 0.1ppm or more, more preferably 1ppm or more, further preferably 5ppm or more, and particularly preferably 10ppm or more. In addition, in order not to reduce transparency, it is preferably 1000ppm or less, more preferably 800ppm or less, further preferably 500ppm or less, and particularly preferably 300ppm or less. The method for determining the content of inorganic particles is the method according to the embodiment.
[0171] The second resin composition solution contains inorganic particles. For good sliding properties when made into a film coil, the content is preferably 1000 ppm or more, more preferably 3000 ppm or more, and further preferably 5000 ppm or more. In addition, from the perspective of cost, it is preferably 50000 ppm or less, more preferably 30000 ppm or less, and further preferably 20000 ppm or less. The method for determining the content of inorganic particles is based on the method of the embodiment.
[0172] The content of inorganic particles contained in the second resin composition solution is greater than the content of inorganic particles contained in the first resin composition solution. The first resin composition solution may or may not contain inorganic particles. When the first resin composition solution contains inorganic particles, the ratio of inorganic particles contained in the first resin composition solution and the second resin composition solution (second resin composition solution / first resin composition solution) is preferably 100 or more, more preferably 200 or more, further preferably 300 or more, and particularly preferably 500 or more. In addition, it is preferably 500,000 or less, more preferably 300,000 or less, and further preferably 100,000 or less.
[0173] The content of the inorganic fine particles contained in the first resin composition solution and the second resin composition solution is the content of the inorganic fine particles contained in the central portion and both end portions of the pre-cut film and the resin film.
[0174] There are no particular limitations on the inorganic particles, and examples thereof include silicon dioxide, carbon, ceramics, etc., among which silicon dioxide is preferred. These may be used alone or in combination of two or more. The average particle size of the inorganic particles is preferably 10 nm or more, more preferably 30 nm or more, and further preferably 50 nm or more. In addition, it is preferably 1 μm or less, more preferably 500 nm or less, and further preferably 100 nm or less. As a commercial product for sale of inorganic particles, for example, colloidal silica "Snowtex (registered trademark) DMAc-ST-ZL" manufactured by Nissan Chemical Industries, Ltd. can be used. It is formed by dispersing inorganic particles in dimethylacetamide. The average particle size is 70 to 100 nm, the dispersion viscosity is 1-10 mPa·S, and contains 20% by mass of SiO2.
[0175] [Cut the front membrane]
[0176] The pre-cutting film according to this embodiment has:
[0177] a central portion composed of a first resin composition,
[0178] At both ends of the central portion, two end portions are formed continuously from the central portion,
[0179] The two end portions are composed of a second resin composition containing inorganic particles,
[0180] The amount of inorganic fine particles added in the two end portions is larger than the amount of inorganic fine particles added in the central portion.
[0181] The pre-cut film can be obtained through the steps A to C of the resin film production method according to the present embodiment.
[0182] Here, "cutting" refers to removing part or all of the portion formed by the second resin composition solution, specifically refers to trimming of both ends of the film in the width direction. In addition, "first resin composition" may refer to the composition (sheet) after the first resin composition solution is dried in step C, and "second resin composition" refers to the composition (sheet) after the second resin composition solution is dried in step C.
[0183] The width of the two end portions (the width of each end portion) is not particularly limited as long as it is a width that can be held in a conventionally known tenter conveyor, and is usually 5 mm or more, and more preferably 10 mm or more. The upper limit of the width is not particularly limited, and for example, the total width of the two ends is 50% or less of the total width of the film, more preferably 30% or less, and even more preferably 10% or less. In addition, it is preferably 0.1% or more, more preferably 0.5% or more, and even more preferably 1% or more.
[0184] The pre-cutting film according to the present embodiment has been described above.
[0185] [Resin film]
[0186] A resin film, characterized in that it has a central portion composed of a first resin composition and
[0187] At both ends of the central portion, two end portions are formed continuously from the central portion,
[0188] The two end portions are composed of a second resin composition containing inorganic fine particles, and the content of the inorganic fine particles in the two end portions is greater than the content of the inorganic fine particles in the central portion.
[0189] Furthermore, any one of the two end portions or the central portion has a cutout portion (cut surface).
[0190] The resin film is a film in which a part or all of the part formed by the second resin composition solution is removed from the film before cutting, and any of the two ends and the central part thereof has a cut-off portion (cut surface). Specifically, it is a film in which a part or all of the two ends are cut off from the structure of "end / central part / end", for example, it has any structure of "end with a part cut off / central part / end", "end with a part cut off / central part / end with a part cut off", "end / central part", "end with a part cut off / central part", "central part", or "central part with a part cut off". Among them, the structure of "end with a part cut off / central part / end", "end with a part cut off / central part / end with a part cut off", "end / central part" or "end with a part cut off / central part" is a partially cut film, and the structure of "central part" or "central part cut off" is a completely cut film.
[0191] The static friction coefficient of the central part of the film before cutting and the resin film is preferably 1 to 2.7, more preferably 1.3 to 2.5. In addition, the friction coefficient of each end portion is preferably 0.5 to 2.5, more preferably 0.7 to 2.0. In addition, the ratio of the friction coefficient of the central part and the two end portions (central part / two end portions) is preferably 1 to 5, more preferably 1.5 to 4. If it is within the above range, when it is wound up as a film roll, the occurrence of wrinkles and sag can be suppressed. It should be noted that the friction coefficient is measured according to the following method.
[0192] The total light transmittance of the resin film is preferably 75% or more. It is more preferably 80% or more, further preferably 85% or more, further preferably 87% or more, and particularly preferably 88% or more. There is no particular upper limit on the total light transmittance, and in industry, it can be 98% or less, and 97% or less is also acceptable.
[0193] The haze of the resin film is preferably 2 or less, more preferably 1.5 or less, further preferably 1 or less, and further preferably 0.8 or less. The lower limit of the haze is not particularly limited, but in industry, 0.01 or more may be sufficient, and 0.05 or more may also be acceptable.
[0194] The yellowness index (YI) of the resin film is preferably 10 or less, more preferably 7 or less, and even more preferably 5 or less. The lower limit of the yellowness index is not particularly limited, but in industry, 0.1 or more may be sufficient, and 0.2 or more may also be acceptable.
[0195] Hereinafter, the present invention will be described in detail using examples, but the present invention is not limited to the following examples unless the gist of the present invention is exceeded.
[0196] <Film thickness measurement method>
[0197] The film thickness was measured using an electronic micrometer Millitron 1245D manufactured by Seiko EM Corporation.
[0198] <Method for measuring coefficient of friction (static friction coefficient)>
[0199] The friction coefficient was measured based on JIS K7125 (1999) - Plastic film and sheet friction coefficient test method. The film surfaces were overlapped, a 100 g weight was placed on the top, the overlapped film below was fixed on a table, and the upper film was moved at 200 mm / min to measure the friction coefficient.
[0200] <Total light transmittance and haze measurement method>
[0201] The total light transmittance and haze of the film were measured using a haze meter NDH2000 manufactured by Nippon Denshoku Co., Ltd. using a CIE standard D65 light source. The same measurement was performed three times, and the arithmetic mean value was used.
[0202] <Yellowness Index (YI) Measurement Method>
[0203] The yellowness of the film was measured using a colorimeter ZE2000 manufactured by Nippon Denshoku Co., Ltd. using a CIE standard C2 light source. The same measurement was performed three times, and the arithmetic mean value was used.
[0204] Example
[0205] [Synthesis Example 1 (Preparation of polyamic acid solution A1)]
[0206] After nitrogen substitution in a reaction vessel having a nitrogen inlet pipe, a reflux pipe and a stirring rod, 32.02 parts by mass of 2,2'-bistrifluoromethyl-4,4'-diaminobiphenyl (TFMB) was dissolved in 279.9 parts by mass of N,N-dimethylacetamide (DMAc), and then 9.81 parts by mass of 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA) and 15.51 parts by mass of 4,4'-oxydiphthalic dianhydride (ODPA) were added in batches in solid form, respectively, and stirred at room temperature for 24 hours. Then, the concentration was adjusted with DMAc to obtain a polyamic acid solution A1 having a solid content of 20% by mass and a reduced viscosity of 3.1 dl / g.
[0207] [Synthesis Example 2 (Preparation of polyamic acid solution A2)]
[0208] To the polyamic acid solution A1 obtained in the same manner as in Synthesis Example 1, 5000 ppm of dimethylacetamide-dispersed silica sol (DMAc-ST-ZL manufactured by Nissan Chemical) was added based on the resin component to prepare a polyamic acid solution A2.
[0209] [Synthesis Example 3 (Preparation of polyimide solution B1)]
[0210] After nitrogen substitution in a reaction container having a nitrogen inlet tube, a thermometer, and a stirring rod, 551 parts by mass of N,N-dimethylacetamide (DMAc) and 64.1 parts by mass of 2,2'-bistrifluoromethyl-4,4'-diaminobiphenyl (TFMB) were added to the reaction container under a nitrogen atmosphere and stirred to dissolve TFMB in DMAc. Then, while stirring in the reaction container, 44.4 parts by mass of 4,4'-(2,2-hexafluoroisopropylidene) diphthalic anhydride (6FDA) and 29.4 parts by mass of biphenyl tetracarboxylic anhydride (BPDA) were added under a nitrogen flow for about 10 minutes, and the polymerization reaction was carried out while the temperature was adjusted to a temperature range of 20 to 40°C and stirring was continued for 6 hours to obtain a viscous polyamic acid solution.
[0211] Then, 410 parts by mass of DMAc was added to the obtained polyamic acid solution for dilution, and then 25.83 parts by mass of isoquinoline as an imidization accelerator was added, and the polyamic acid solution was kept at a temperature range of 30 to 40° C. while being stirred. Here, 122.5 parts by mass of acetic anhydride was slowly added dropwise as an imidization agent over about 10 minutes, and then, the liquid temperature was further kept at 30 to 40° C. while stirring was continued for 12 hours to carry out a chemical imidization reaction, thereby obtaining a polyimide solution.
[0212] Then, 1000 parts by mass of the obtained polyimide solution containing the imidizing agent and the imidizing accelerator was transferred to a reaction vessel equipped with a stirring device and a stirring blade, and the temperature was maintained at 15 to 25°C while stirring at a speed of 120 rpm. At this time, 1500 parts by mass of methanol were added dropwise at a rate of 10 g / min. When about 800 parts by mass of methanol were added, the turbidity of the polyimide solution was confirmed, and the precipitation of the powdered polyimide was confirmed. 1500 parts by mass of methanol were continued to be added to completely precipitate the polyimide. Subsequently, the contents of the reaction vessel were filtered through a suction filter, and further washed / filtered with 1000 parts by mass of methanol. After that, 50 parts by mass of the filtered polyimide powder was dried at 50°C for 24 hours using a dryer connected to a local exhaust device, and further dried at 260°C for 2 hours to remove the remaining volatile components to obtain a polyimide powder. The reduced viscosity of the obtained polyimide powder was 2.1 dl / g. Then, 42 parts by mass of the obtained polyimide powder was dissolved in 168 parts by mass of DMAc to obtain a polyimide solution B1 having a solid content of 20 parts by mass.
[0213] [Synthesis Example 4 (Preparation of polyimide solution B2)]
[0214] To the polyimide solution B1 obtained in the same manner as in Synthesis Example 3, 5000 ppm of dimethylacetamide-dispersed silica sol (DMAc-ST-ZL manufactured by Nissan Chemical Industries, Ltd.) was added based on the resin component to prepare a polyimide solution B2.
[0215] [Synthesis Example 5 (Preparation of polyimide solution C1)]
[0216] In a reaction container equipped with a nitrogen inlet tube, a Dean-Stark apparatus, a reflux tube, and a stirring rod, 12.42 parts by mass of 4,4'-diaminodiphenyl sulfone (4,4'-DDS), 12.42 parts by mass of 3,3'-diaminodiphenyl sulfone (3,3'-DDS), and 75 parts by mass of γ-butyrolactone (GBL) were added while introducing nitrogen. Subsequently, 24.82 parts by mass of 4,4'-oxydiphthalic dianhydride (ODPA), 5.88 parts by mass of biphenyl tetracarboxylic anhydride (BPDA), 33.5 parts by mass of GBL, and 39 parts by mass of toluene were added at room temperature, and the temperature was raised to an internal temperature of 160°C, and refluxed for 1 hour at 160°C to carry out imidization. After the imidization was completed, the temperature was raised to 180°C, and the reaction was continued while removing toluene. After 12 hours of reaction, the mixture was taken out from the oil bath and returned to room temperature, and 114.9 parts by mass of GBL was added to a solid content concentration of 20% by mass to obtain a polyimide solution C1 having a reduced viscosity of 0.6 dl / g.
[0217] [Synthesis Example 6 (Preparation of polyimide solution C2)]
[0218] To the polyimide solution B1 obtained in the same manner as in Synthesis Example 5, 5000 ppm of dimethylacetamide-dispersed silica sol (DMAc-ST-ZL manufactured by Nissan Chemical Industries, Ltd.) was added based on the resin component to prepare a polyimide solution C2.
[0219] [Synthesis Example 7 (Preparation of polyamic acid solution D1)]
[0220] In a reaction container equipped with a nitrogen inlet tube, a Dean-Stark apparatus, a reflux tube, and a stirring rod, 38.44 parts by mass of norbornane-2-spiro-α-cyclopentanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic dianhydride (CpODA), 34.85 parts by mass of 9,9-bis(4-aminophenyl)fluorene (BAFL), 3.60 parts by mass of triethylamine, 146.5 parts by mass of N-methyl-2-pyrrolidone (NMP), 146.5 parts by mass of γ-butyrolactone (GBL), and 360 parts by mass of toluene were added at room temperature while introducing nitrogen. The internal temperature was then raised to 180° C., and the mixture was heated at 180° C. for 3 hours while distilling off toluene to carry out imidization, thereby obtaining a polyimide solution.
[0221] Then, 250 parts by mass of the obtained polyimide solution was transferred to a reaction vessel equipped with a stirring device and a stirring wing, and stirred at a speed of 120 rpm while maintaining a temperature of 15 to 25°C, and 5000 parts by mass of acetone was added thereto at a rate of 10 g / min. When about 250 parts by mass were added, the turbidity of the polyimide solution was confirmed, and the precipitation of the powdered polyimide was confirmed. The remaining 250 parts by mass of acetone were continued to be added to completely precipitate the polyimide. Subsequently, the contents of the reaction vessel were filtered through a suction filter, and further washed / filtered with 200 parts by mass of methanol. Then, 30 parts by mass of the filtered polyimide powder was dried at 50°C for 24 hours using a dryer connected to a local exhaust device, and further dried at 260°C for 2 hours to remove the remaining volatile components to obtain a polyimide powder. The reduced viscosity of the obtained polyimide powder was 0.7 dl / g. Then, 4.2 parts by mass of the obtained polyimide powder was dissolved in 16.8 parts by mass of NMP to obtain a polyimide solution D1 having a solid content of 20% by mass and a reduced viscosity of 0.7 dl / g.
[0222] [Synthesis Example 8 (Preparation of polyamic acid solution D2)]
[0223] To the polyamic acid solution D1 obtained in the same manner as in Synthesis Example 7, 5000 ppm of dimethylacetamide-dispersed silica sol (DMAc-ST-ZL manufactured by Nissan Chemical) was added based on the resin component to prepare a polyamic acid solution D2.
[0224] [Synthesis Example 9 (Preparation of polyamic acid solution E1)]
[0225] After nitrogen substitution in a reaction container equipped with a nitrogen inlet tube, a thermometer, and a stirring rod, 196.1 parts by mass of 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA), 227.3 parts by mass of 4-amino-N-(4-aminophenyl)benzamide (DABAN), and 1694 parts by mass of N,N-dimethylacetamide were added to the reaction container under a nitrogen atmosphere and dissolved, followed by stirring at room temperature for 24 hours to obtain a polyamic acid solution E1 with a solid content of 20% by mass and a reduced viscosity of 4.5 dl / g.
[0226] [Synthesis Example 10 (Preparation of polyimide solution E2)]
[0227] To the polyimide solution D1 obtained in the same manner as in Synthesis Example 7, 5000 ppm of dimethylacetamide-dispersed silica sol (DMAc-ST-ZL manufactured by Nissan Chemical Industries, Ltd.) was added relative to the resin component to prepare a polyimide solution E2.
[0228] (Example 1)
[0229] Polyamic acid solution A1 and polyamic acid solution A2 were prepared. On a support PET film (A4100 manufactured by Toyobo Co., Ltd.) having a central width of 500 mm, a Figure 1 , Figure 2 The comma coater shown in the figure was used to coat the polyamic acid solution A1 with the gap adjusted so that the final film thickness was 25 μm, and at the same time, the polyamic acid solution A2 was coated on the 50 mm width of both ends so that the final film thickness was 35 μm. At this time, a side plate with a side plate width of 10 mm was used.
[0230] The polyamic acid film was then dried at 100-110°C for 10 minutes to obtain a polyamic acid film, which was then rolled up on a 6-inch ABS core together with the PET film to obtain a polyamic acid film roll. The polyamic acid film and the PET film were unwound from the obtained polyamic acid film roll, and the self-supporting polyamic acid film was peeled off from the PET film to obtain a polyamic acid film.
[0231] The obtained polyamic acid film was passed through a pin tenter, which had a pin plate with pins arranged in parallel at a fixed interval, and the pins were inserted into the ends of the film for holding, and the pin plate interval was adjusted in a manner that the film would not break and unnecessary relaxation would not occur, and the film was conveyed in a manner that the final pin interval was 570 mm, and heated under the conditions of 200° C. for 3 minutes as the first section, 250° C. for 3 minutes as the second section, 300° C. for 3 minutes as the third section, and 350° C. for 3 minutes as the fourth section to carry out imidization reaction. Then, it took 2 minutes to cool to room temperature, and then, a part of the film end formed by the polyamic acid solution A2 was trimmed, and 25 mm was left at each end and wound up together with the central part to obtain a polyimide film with a thickness of 25 μm and a width of 550 mm.
[0232] (Example 2)
[0233] Prepare polyamic acid solution A1 and polyamic acid solution A2. Figure 7 , Figure 8 The comma coater shown in the figure was used to apply polyamic acid solution A2 to both ends so that the final film thickness was 35 μm, and then polyamic acid solution A1 was applied to the center with a T-die head with a gap adjusted so that the final film thickness was 25 μm. At this time, the coating was applied with a width of 1000 mm in the center and 50 mm at both ends.
[0234] The film was then dried at 100 to 110° C. for 10 minutes and peeled off from the support after drying to obtain a self-supporting polyamic acid film.
[0235] The obtained pre-cut film was passed through a pin tenter, which had pin plates arranged with pins at a fixed interval when the pin plates were arranged in parallel, and the pins were inserted into the ends of the film to hold it, and the pin plate interval was adjusted so that the film would not break and unnecessary relaxation would not occur, and the film was conveyed in a manner of a final pin interval of 1080 mm, and heated under the conditions of 200° C. for 3 minutes as the first section, 250° C. for 3 minutes as the second section, 300° C. for 3 minutes as the third section, and 350° C. for 3 minutes as the fourth section to carry out an imidization reaction. Then, it took 2 minutes to cool to room temperature, and then, a part of the end of the film formed by the polyamic acid solution A2 was trimmed, leaving 25 mm at each end and the central part, and continuously wound up on a 3-inch ABS resin core into a coil, to obtain a polyimide film with a thickness of 25 μm, a width of 1050 mm, and a length of 500 m.
[0236] (Example 3)
[0237] Prepare polyamic acid solution A1 and polyamic acid solution A2. Fig. 9 , Fig.10The polyamic acid solution A2 was applied to both ends using the T-die shown in the figure so that the final film thickness was 35 μm, and then the polyamic acid solution A1 was applied to the center with the T-die adjusting the gap so that the final film thickness was 25 μm. At this time, the coating was 1000 mm in the center and 50 mm in the ends.
[0238] The film was then dried at 100 to 110° C. for 10 minutes and peeled from the support after drying to obtain a self-supporting polyamic acid film.
[0239] The obtained pre-cut film was passed through a pin tenter, which had pin plates arranged with pins at a fixed interval when the pin plates were arranged in parallel, and the pins were inserted into the ends of the film to hold it, and the pin plate interval was adjusted so that the film would not break and unnecessary relaxation would not occur, and the film was conveyed in a manner where the final pin interval was 1080 mm, and heated under the conditions of 200° C. for 3 minutes as the first section, 250° C. for 3 minutes as the second section, 300° C. for 3 minutes as the third section, and 350° C. for 3 minutes as the fourth section to carry out imidization reaction. Then, it took 2 minutes to cool to room temperature, and then, a part of the end of the film formed by the polyamic acid solution A2 was trimmed, leaving 25 mm at each end and the central part, and continuously wound up on a 3-inch ABS resin core into a coil, to obtain a polyimide film with a thickness of 25 μm, a width of 1050 mm, and a length of 500 m.
[0240] (Example 4)
[0241] Polyimide solution B1 and polyimide solution B2 were prepared. The same operation as in Example 1 was performed, except that polyimide solution B1 was used instead of polyamic acid solution A1 and the gap was adjusted so that the final film thickness was 45 μm, and polyimide solution B2 was used instead of polyamic acid solution A2 so that the final film thickness was 60 μm, to obtain a polyimide film having a thickness of 45 μm and a width of 550 mm.
[0242] (Example 5)
[0243] Polyimide solution C1 and polyimide solution C2 were prepared. The same operation as in Example 1 was performed except that polyimide solution C1 was used instead of polyamic acid solution A1 and the gap was adjusted to coat the final film thickness to be 20 μm, and polyimide solution C2 was used instead of polyamic acid solution A2 to make the final film thickness 30 μm, to obtain a polyimide film with a thickness of 20 μm and a width of 550 mm.
[0244] (Example 6)
[0245] Polyamic acid solution D1 and polyamic acid solution D2 were prepared. The same operation as in Example 1 was performed except that polyamic acid solution D1 was used instead of polyamic acid solution A1, and the gap was adjusted so that the final film thickness was 20 μm, and polyimide solution D2 was used instead of polyamic acid solution A2 so that the final film thickness was 30 μm, to obtain a polyimide film with a thickness of 20 μm and a width of 550 mm.
[0246] (Example 7)
[0247] Polyamic acid solution E1 and polyamic acid solution E2 were prepared. The same operation as in Example 1 was performed, except that polyamic acid solution E1 was used instead of polyamic acid solution A1 and the gap was adjusted so that the final film thickness was 22 μm, and polyamic acid solution E2 was used instead of polyamic acid solution A2 so that the final film thickness was 35 μm, to obtain a polyimide film with a thickness of 22 μm and a width of 550 mm.
[0248] (Example 8)
[0249] A polyimide film having a thickness of 25 μm and a width of 550 mm was obtained in the same manner as in Example 1 except that the polyamic acid solution A2 was applied so as to have a final film thickness of 25 μm.
[0250] (Comparative Example 1)
[0251] A polyimide film having a thickness of 25 μm and a width of 550 mm and containing no lubricant in the entire central portion and both end portions was obtained in the same manner as in Example 1 except that the polyamic acid solution A1 was used instead of the polyamic acid solution A2.
[0252] (Comparative Example 2)
[0253] A polyimide film having a thickness of 25 μm and a width of 550 mm containing a lubricant in the entire area of the center and both ends was obtained in the same manner as in Example 1 except that the polyamic acid solution A2 was used instead of the polyamic acid solution A1.
[0254] (Comparative Example 3)
[0255] The same operation as in Example 1 was performed except that polyamic acid solutions A1 and A2 were used, and A1 was applied to both ends and A2 was applied to the center, thereby obtaining a polyimide film having a thickness of 25 μm and a width of 550 mm, containing a lubricant in the center and not containing a lubricant in both ends.
[0256] [Synthesis Example 11 (Preparation of polyamic acid solution F1)]
[0257] After nitrogen substitution in a reaction container equipped with a nitrogen inlet tube, a reflux tube, and a stirring rod, 980.6 parts by mass of 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA), 1029 parts by mass of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 465.3 parts by mass of 4,4'-oxydiphthalic dianhydride (ODPA), 3202.4 parts by mass of 2,2'-bistrifluoromethyl-4,4'-diaminobiphenyl (TFMB), and 32171 parts by mass of N,N-dimethylacetamide were added to the reaction container under a nitrogen atmosphere and dissolved, and then stirred at room temperature for 24 hours to perform a polymerization reaction, thereby obtaining a polyamic acid solution F1 having a reduced viscosity of 3.50 dl / g.
[0258] [Synthesis Example 12 (Preparation of polyimide solution F2)]
[0259] To the polyimide solution F1 obtained in the same manner as in Synthesis Example 11, 5000 ppm of dimethylacetamide-dispersed silica sol (DMAc-ST-ZL manufactured by Nissan Chemical Industries, Ltd.) was added based on the resin component to prepare a polyimide solution F2.
[0260] (Example 9)
[0261] Polyamic acid solution F1 and polyamic acid solution F2 were prepared. The same operation as in Example 1 was performed, except that polyamic acid solution F1 was used instead of polyamic acid solution A1 and the gap was adjusted so that the final film thickness was 22 μm, and polyamic acid solution F2 was used instead of polyamic acid solution A2 so that the final film thickness was 35 μm, to obtain a polyimide film having a thickness of 22 μm and a width of 550 mm.
[0262] [Synthesis Example 13 (Preparation of polyamic acid solution G1)]
[0263] A bi-tower type silsesquioxane derivative (AASQ1) containing an acid anhydride group represented by the structure of formula (1) was purchased from Japan Materials Technology Co., Ltd.
[0264] [Chemistry 1]
[0265]
[0266] Then, after nitrogen substitution in a reaction container having a nitrogen inlet tube, a reflux tube, and a stirring rod, 327.2 parts by mass of cyclohexanetetracarboxylic dianhydride (PMDA), 490.2 parts by mass of 2,2'-bistrifluoromethyl-4,4'-diaminobiphenyl (TFMB), 45.4 parts by mass of AASQ1, and 5340 parts by mass of N-methyl-2-pyrrolidone were added to the reaction container under a nitrogen atmosphere and dissolved, and then stirred at room temperature for 24 hours to carry out a polymerization reaction, thereby obtaining a polyamic acid solution G1 having a reduced viscosity of 1.46 dl / g.
[0267] [Synthesis Example 14 (Preparation of polyamic acid solution G2)]
[0268] To the polyamic acid solution G1 obtained in the same manner as in Synthesis Example 13, 5000 ppm of dimethylacetamide-dispersed silica sol (DMAc-ST-ZL manufactured by Nissan Chemical) was added based on the resin component to prepare a polyamic acid solution G2.
[0269] [Synthesis Example 15 (Preparation of polyamic acid solution H1)]
[0270] A bi-tower type silsesquioxane derivative (AMSQ1) containing an amino group represented by the structure of formula (2) was produced according to the method described in Japanese Patent Application Laid-Open No. 2006-265243.
[0271] [Chemistry 2]
[0272]
[0273] Then, after nitrogen substitution in a reaction container having a nitrogen inlet tube, a reflux tube, and a stirring rod, 325.6 parts by mass of pyromellitic dianhydride (PMDA), 470.8 parts by mass of 2,2'-bistrifluoromethyl-4,4'-diaminobiphenyl (TFMB), 39.9 parts by mass of AMSQ1, and 6880 parts by mass of N-methyl-2-pyrrolidone were added to the reaction container under a nitrogen atmosphere and dissolved, and then stirred at room temperature for 24 hours to carry out a polymerization reaction, thereby obtaining a polyamic acid solution H1 having a reduced viscosity of 3.50 dl / g.
[0274] [Synthesis Example 16 (Preparation of polyamic acid solution H2)]
[0275] To the polyamic acid solution H1 obtained in the same manner as in Synthesis Example 15, 5000 ppm of dimethylacetamide-dispersed silica sol (DMAc-ST-ZL manufactured by Nissan Chemical Industries, Ltd.) was added relative to the resin component to prepare a polyamic acid solution H2.
[0276] (Example 10)
[0277] Polyamic acid solution G1 and polyamic acid solution G2 were prepared. The same method as in Example 1 was followed, except that polyamic acid solution G1 was used instead of polyamic acid solution A1 to adjust the gap and apply the polyamic acid solution so that the final film thickness was 22 μm, and polyamic acid solution G2 was used instead of polyamic acid solution A2 to make the final film thickness 35 μm, to obtain a polyimide film having a thickness of 22 μm and a width of 550 mm.
[0278] (Example 11)
[0279] Polyamic acid solution H1 and polyamic acid solution H2 were prepared. The same operation as in Example 1 was performed, except that polyamic acid solution H1 was used instead of polyamic acid solution A1 and the gap was adjusted so that the final film thickness was 22 μm, and polyamic acid solution H2 was used instead of polyamic acid solution A2 so that the final film thickness was 35 μm, to obtain a polyimide film having a thickness of 22 μm and a width of 550 mm.
[0280] <Evaluation of film winding (film status)>
[0281] ○: No wrinkles or winding deviation during winding
[0282] △: There are slight wrinkles or winding deviation during winding
[0283] ×: Creases occur during winding and winding is impossible
[0284] [Table 1]
[0285]
[0286] The polyimide films of Examples 1 to 11 have a greater film thickness at both ends formed by the second resin composition solution than at the center formed by the first resin composition solution, and can be wound up without losing optical properties or generating wrinkles by adding a lubricant to both ends formed by the second resin composition solution. The polyimide film of Example 8 has the same film thickness at the center and both ends, which results in minute wrinkles when wound up. However, by adding a lubricant to both ends formed by the second resin composition solution, the film can be wound up without deteriorating the optical properties. On the other hand, the polyimide films of Comparative Examples 1 to 3 have problems with wrinkles or deterioration of optical properties due to inappropriate addition of lubricants at both ends and the center.
Claims
1. A method for producing a resin film, characterized in that: have: Step A of applying a first resin composition solution to the center of the support, Step B: applying a second resin composition solution containing inorganic fine particles to both end portions of the support adjacent to the central portion; Step C of drying the first resin composition solution and the second resin composition solution to obtain a pre-cut film laminate, Step D of peeling the pre-cutting film laminate from the support to obtain a pre-cutting film, After the step D, the two ends of the pre-cut film are held by a tenter conveyor. Step F of conveying the pre-cut film while both ends of the pre-cut film are held. and after the step F, a step G of removing part or all of the portion formed by the second resin composition solution from the pre-cut film; The content of inorganic fine particles in the first resin composition solution is 300 ppm or less, The content of the inorganic fine particles in the second resin composition solution is 1000 ppm or more and 50000 ppm or less, The average particle size of the inorganic fine particles is not less than 10 nm and not more than 1 μm. The film thickness of the central portion of the film before cutting is 5 μm to 125 μm, and the film thickness of the two end portions is 10 μm to 200 μm. The film thickness at both ends is almost the same as that at the central portion, or is smaller than that at the central portion, or the film thickness at one end is larger than that at the central portion, and the film thickness at the other end is smaller than that at the central portion.
2. The method for producing a resin film according to claim 1, wherein: The content of the inorganic fine particles in the first resin composition solution is 0.1 ppm or more.
3. The method for producing a resin film according to claim 1, wherein: The content of the inorganic fine particles in the second resin composition solution is 5000 ppm or more and 20000 ppm or less.
4. The method for producing a resin film according to any one of claims 1 to 3, wherein: The first resin composition is a polyimide-based resin.
5. A pre-cut film, characterized in that: have: a central portion composed of a first resin composition, and At both ends of the central portion, two end portions are formed continuously from the central portion, The two end portions are composed of a second resin composition containing inorganic particles, The content of inorganic fine particles in the first resin composition solution is 300 ppm or less, The content of the inorganic fine particles in the second resin composition solution is 1000 ppm or more and 50000 ppm or less, The average particle size of the inorganic fine particles is not less than 10 nm and not more than 1 μm. The film thickness of the central portion is 5 μm to 125 μm, and the film thickness of the two end portions is 10 μm to 200 μm. The film thickness at both ends is almost the same as that at the central portion, or is smaller than that at the central portion, or the film thickness at one end is larger than that at the central portion, and the film thickness at the other end is smaller than that at the central portion.
6. The pre-cut film according to claim 5, characterized in that: The first resin composition is a polyimide-based resin. 7 . A partially cut film comprising a cut portion on the pre-cut film according to claim 5 or 6 .
Citation Information
Patent Citations
Improved heat-resistant polyimide film
JP1994011800B2
Polyimide film, manufacturing method therefor and use applications thereof
JP2002234040A
Organosilicon compound having cage-form silicon skeleton and macromolecular compound therefrom
JP2006265243A
Phase difference film, polarizing plate, liquid crystal panel, and liquid crystal display device
JP2008292751A
Optical film and method for manufacturing the same
JP2011248198A